2021
DOI: 10.1088/1361-6668/abdcc4
|View full text |Cite
|
Sign up to set email alerts
|

Using a Josephson junction as an effective on-chip temperature sensor

Abstract: Temperature sensing and control are essential in experiments running in cryocooled systems, as with the case of liquid helium-free superconducting devices. A Josephson junction as on-chip temperature sensor operated in ac provides the highest sensitivity and minimal power loading to the cryogenic environment, thanks to the noise rejection of lock-in detection. To demonstrate the advantages of on-chip sensing, we tested it with a Josephson voltage standard array in cryocooler and compared with the conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In addition, one of the two available JAWS array was investigated as on-chip temperature sensor, in a similar way as described in Ref. [13]. This would ensure the stabilization of the actual chip temperature even when microwave pulses are applied to the junctions, which is particularly critical at lower temperatures, owing to the reduced thermal conduction.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, one of the two available JAWS array was investigated as on-chip temperature sensor, in a similar way as described in Ref. [13]. This would ensure the stabilization of the actual chip temperature even when microwave pulses are applied to the junctions, which is particularly critical at lower temperatures, owing to the reduced thermal conduction.…”
Section: Resultsmentioning
confidence: 99%
“…More recent studies have shown that thermal issues in cryocooler operation of quantum standards can be tackled directly by a refined control of the average temperature of the chip [40]: the latter can be monitored and stabilized using Josephson junctions as thermal sensor, thanks to the strong dependence of electrical parameters with temperature in the superconducting state. Also, on-chip active compensation of temperature fluctuations, caused by the cooling cycle exploited by the cryocooler, is underway to cancel the annoying effect of Josephson junction IV curves "breathing" in phase with the cryocooler motion, causing the current-amplitude of quantum voltages steps to be largely reduced and, in the worst case, completely unusable.…”
Section: Cryocooler Operationmentioning
confidence: 99%
“…Proper operation of a Josephson standard in cryocooler is always a challenging task, owing to the tight thermalization requirements [30,31] alongside the need of supplying non negligible dc and rf power for proper operation. We addressed the issue of designing an optimized cryopackage for maximizing the thermal contact between the chip and the cooling surface [32].…”
Section: Pulsed Standards Toward Rfmentioning
confidence: 99%